Analysis of Main Components in Jujube and Mulberry Extracts by High-Sensitive HPLC-ESI-Q-TOF-MS/MS. (17th February 2021) - Li, Ran; Wei, Min; Guo, Guoning; Li, Yi; Pan, Xi; Song, Xuyan; Rong, Lin; Chen, Yi; Chen, Beibei
Abstract: In order to comprehensively reflect the cigarette quality, a method combining direct injection of diluted sample with high sensitive high-performance liquid chromatography (HPLC)- electrospray (ESI)- quadrupole (Q)- time of flight (TOF)- tandem mass spectrometry (MS/MS) was developed for the identification of major components of cigarette essences (jujube and mulberry extracts). Based on the observed relative molecular mass, MS/MS fragmentation behavior, MS/MS database and related literatures, the components of the jujube extract and mulberry extract were identified. The result shows that the composition of jujube extract and mulberry extract has some similarity. They all mainly contain amino acids, free amino compounds and Maillard reaction products, which are the main constituents of a cigarette essence.